Phenolic compounds present in fruit extracts of Malus spp. show antioxidative and pro‐apoptotic effects on human gastric cancer cell lines. Issue 11 (1st September 2019) - Han, Meiling; Li, Ai; Shen, Ting; Meng, Jiaxin; Lei, Yongqin; Zhang, Xian; Liu, Pengyuan; Gan, Linxin; Ao, Lei; Li, Houhua
Abstract: The study aims to analyze the phenolic compounds in Malus spp. and evaluate their antioxidant and pro‐apoptotic effects in BGC‐803 gastric cancer cells. The results showed that cyanidin‐3‐galactoside was the main polyphenol in Malus "Royalty" (MR), while catechin, epicatechin, and proanthocyanidin B1 and B2 contents were higher in Malus "Cinnabar" (MC) and Malus micromalus (MM) than in MR fruits. The total polyphenol content, total flavonoid content, and antioxidative properties of Malus spp. fruits followed an order of MR > MC > MM. Fruit extracts could inhibit BGC‐803 cells growth and induce apoptosis, with IC50 values of 0.47, 0.36, and 0.31 mg/ml for MR, MC, and MM, respectively. Furthermore, fruit extracts induced cell apoptosis through increasing Bcl‐2 and Bcl‐xl (pro‐apoptosis) expression and inhibiting Bax and Bak (anti‐apoptosis) expression, thereby accelerating cell apoptosis. Taken together, these results demonstrate that red fruits (i.e., MR and MC) were more effective against cancer cells than green fruits (i.e., MM). Practical applications: Fruits of Malus spp. are ≤5 cm in size, considerably smaller than apples. They are rich in various natural bioactive compounds that are often consumed as a dietary supplement or used as natural raw materials for function food. In the current study, it is comprehensively characterized profile and bioactivity of phenolic metabolites in Malus spp. fruits of different colors, and found that red fruits are more effective in reducing the free radicals and inducing cancer cells apoptosis than green fruits. These findings are valuable for food technologists and food manufacturers, especially those who produce crabapple supplement. The study investigated the molecular mechanism of how Malus spp. fruits exert anti‐cancer functions. This lays a theoretical foundation for future research on developing anti‐cancer function food and provides helpful guidance for fruit market management and fruit processing industry.